A Novel Mutation c.841C>T in COPA Syndrome of an 11-Year-Old Boy: A Case Report and Short Literature Review - Zeng, Jingxia; Hao, Jing; Zhou, Wei; Zhou, Zhaoqun; Miao, Hongjun (Frontiers in Pediatrics, 2021)
COPA syndrome is a rare autosomal dominant disorder with auto-immune and auto-inflammatory abnormalities. This disease is caused by mutations of COPα, a protein that functions in the retrograde transport from the Golgi to the ER. Here we report the first COPA case of an 11-year-old boy with c.841C>T, p.R281W mutation. The arginine at position 281 was located in a highly evolutionary-conserved region. Immunosuppressive drugs and corticosteroids might not improve the long-term outcome of COPA patients. For patients with pulmonary disease, polyarthritis and/or kidney disorder, and suspected of COPA, genetic analysis should be conducted promptly for early diagnosis.